One Building at A Time for Tambak Lorok - HN Nurul Huda Putu Ekapraja; Etika Sukma Adiyanti; Ardefian Piradipta Suharno (International Conference on Coastal and Delta Areas, 2017)
Global warming causes climate change and sea level rise. This is a threat for coastal regions, especially for coastal settlements with activities that are influenced by this natural phenomenon. Consequences are damage of houses, humid house environment, sustainability of the houses, obstructed economic activities and domestic works, disruption of sanitation facilities, lack of electricity, failure of transport system, psychological issues and other. Icons Tambak Lorok as